EFFECT OF PEER SUPPORT GROUP ON ACADEMIC STRESS AMONG GRADE II VOCATIONAL HIGH SCHOOL ADOLESCENTS - Purnomo; purnomo, purnomo; Suciati, Suciati; Herminaju, Ketjuk; Fayakun, Fayakun (Jurnal Penelitian, 2025)
Background: Academic stress is a phenomenon that often occurs in school-age adolescents. Academic stress is a condition where students cannot face academic demands and perceive the academic demands as disturbances. Method:  This research was conducted by a researcher who used student respondents who were divided into two intervention groups, 141 respondents, and a control group of 141 respondents. This study used by Zung Self-Rating Anxiety Scale (ZSRAS) questionnaire. In this research design was used by Quasi with a Control Group Pre-Post Test with Peer Support Group intervention. Sampling technique using by Simple Random Sampling using Lottery Technique with inclusion and ekslusion criteria of respondents and using analysis with SPSS using a Pearson product-moment correlation analysis test. Stress level in the control group was obtained P = 0.513 > 0.05, while stress level in the intervention group before and after intervention in the intervention group was obtained P = 0.003 < 0.05, differed in effect stress levels in control and intervention groups. Conclusion: Peer support groups can provide positive support to students who have experienced academic stress due to learning. It is a system for providing assistance with respect, shared responsibility, and mutual agreement, namely through support, friendship, empathy, sharing, and mutual assistance. Peer support groups provide social, emotional support, instrumental support and sharing in any condition in bringing about the desired social or personal change.